Behind the Shadow of Stories: Production of Fantastic Stories : Tras la sombra de las historias: producción de cuentos fantásticos (Papeles, 2022)
Introduction: This research aims to determine the incidence of a didactic sequence, with a communicative approach, in the oral production of fantastic stories, of the children of the garden room 2, of the Child Development Center Harvesting Dreams of Puerto Caldas, Pereira and reflect on the language teaching practices of the research teacher. Methodology: For this, a quantitative methodological approach is chosen, with a pre-experimental intra-group design, pretest and Post-Test type. For the collection of information, an assessment grid was designed for the oral production of fantastic stories by 11 boys and girls, based on the following dimensions: Plane of history and Discursive Linguistics. Results and discussion: For the quantitative analysis, descriptive statistics were applied, from which the Working Hypothesis was validated, concluding that the didactic sequence of communicative approach had an impact on the improvement of oral productions of fantastic stories of children. Conclusions: In the analysis, the teacher reflected on the practices and the way to solve eventualities to favor the production processes.
Keywords: Fantastic story; oral production; didactic sequence; communicative approach; preschool